THE IMPACT OF THE DIGITAL ECONOMY ON POPULATION HEALTH - Zyurin E.A.; Abramova T.F.; Maltsev D.A.; Petruk E.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the level of physical fitness of the population in the digital economy. Methods and structure of the study. The scientific work involved 140 men and 140 women aged 25 to 59 years. The study participants belong to two areas of work with different levels of physical activity. All are admitted to physical education and sports and live in the Vladimir, Moscow, Smolensk regions and the city of Moscow. Results and conclusions. The study did not reveal any significant differences between the morphofunctional indicators, physical activity and the level of physical fitness in people who mainly use IT technologies in the process of work and everyday activities, and people who do not identify themselves with digital processes. Therefore, when developing programs to improve the physical fitness of the population, in the digital economy, it is necessary to take into account the trends towards an increase in general physical activity in the context of automation of all aspects of life, including indicators of physical fitness that ensure a person performs basic social functions without risk to health.